2016
DOI: 10.1111/mec.13663
|View full text |Cite
|
Sign up to set email alerts
|

The role of isoforms in the evolution of cryptic coloration in Peromyscus mice

Abstract: A central goal of evolutionary biology is to understand the molecular mechanisms underlying phenotypic adaptation. While the contribution of protein-coding and cis-regulatory mutations to adaptive traits has been well documented, additional sources of variation - such as the production of alternative RNA transcripts from a single gene, or isoforms - have been understudied. Here, we focus on the pigmentation gene Agouti, known to express multiple alternative transcripts, to investigate the role of isoform usage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 54 publications
4
21
0
2
Order By: Relevance
“…While our study helped investigate the contribution of cis -regulatory divergence to adaptive traits, technical advances will enable us to advance our understanding of the genetic basis of phenotypic evolution, for example by investigating the role of isoforms in adaptive evolution (Gao et al. 2015; Mallarino et al. 2016) and offer an integrative view of the interactions between regulatory mechanisms and alternative transcription.…”
Section: Resultsmentioning
confidence: 99%
“…While our study helped investigate the contribution of cis -regulatory divergence to adaptive traits, technical advances will enable us to advance our understanding of the genetic basis of phenotypic evolution, for example by investigating the role of isoforms in adaptive evolution (Gao et al. 2015; Mallarino et al. 2016) and offer an integrative view of the interactions between regulatory mechanisms and alternative transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Fine mapping of this variation revealed that not only the Agouti locus is the major driver of pigment variation (Manceau et al 2011) but also this genetic region decomposes itself into multiple noncoding sub-loci, each tightly associated with parts of the total phenotype (Linnen et al 2013). Various regulatory elements are involved in directing the expression of three alternative isoforms into different body regions (Mallarino et al 2016). Each adaptive allele is a complex haplotype that is inherited as a package that underwent multiple local changes.…”
Section: Cis-regulatory Evolution Drives Regional Specific Color Shiftsmentioning
confidence: 99%
“…The hair-cycle isoform, containing noncoding exons 1B/1C, is expressed in both the dorsal and ventral dermis during hair growth, and is required for forming light, pheomelanin bands on individual hairs ( Bultman et al 1994 ; Vrieling et al 1994 ). In Peromyscus , these same isoforms are present as well as additional, novel isoforms ( Mallarino et al 2017 ). Isoform-specific changes in Agouti expression are associated with changes in the dorsal–ventral boundary (ventral isoform; Manceau et al 2011 ) and the width of light bands on individual hairs (hair-cycle isoform; Linnen et al 2009 ).…”
Section: Resultsmentioning
confidence: 99%